Effect of Vitamin D3 Enrichment by Ultra Violet Blue (UVB) Radiation and Dietary Zinc Supplementation on Egg Production and Feed Consumption in Layer Birds - P. S. Megha; V. Ramnath; K. V. Vishnudas (Archives of Current Research International, 2024)
Nutritionists have recently been involved in enriching or altering the nutritional profile of poultry products, such as meat and eggs, in relation to increased consumer interest in the nutritional value of foods. Newer technologies like development of designer eggs were exploited beyond their traditional food value. Designer eggs are those that have modified contents from standard egg according to the consumers’ preference or according to current market demand. The present study to evaluate the influence of vitamin D3 enrichment by UVB radiation and dietary zinc supplementation on egg production and feed consumption in layer birds was conducted at Department of Veterinary Physiology, College of Veterinary and Animal Sciences, Mannuthy, for a period of 12 weeks from 01 February 2020 to 01 May 2020. A total of sixty-four laying hens, belonging to crossbred (White Leghorn N strain and Desi) housed in animal house attached to the department were used in the experiment. The treatments of this study included a control diet (according to BIS 2007) fed group (group I), a group with zinc supplementation alone (group II), a group with UVB exposure without zinc supplementation (group III) and a group with both UVB exposure and zinc supplementation (group IV). The four treatments were tested in 28-week-old crossbred hens in a completely randomised experimental design. Each of the experimental treatments had four replicates with four birds with all standard managemental conditions. The statistical analysis showed that egg production was not significantly affected by UVB light exposure and dietary zinc supplementation. However, the effect of UVB exposure and zinc supplementation via feed was highly significant (p≤0.01) for feed consumption. The highest overall mean feed intake (113.18±0.14 g/day) was recorded with those birds exposed to UVB and fed with inorganic zinc. While the lowest value (107.17±0.24 g/day) was recorded in group of birds fed with zinc supplementation in diet without UVB exposure. As a future prospective we can study the egg production rate and feed consumption rate in layer chicken that are intended for different types of designer egg production.